Anatomical characteristics of mitral isthmus and its spatial relationship with the esophagus in patients undergoing atrial fibrillation ablation using CT angiography - Yilin Pan; Yilin Pan; Hong Zeng; Xin Liu; Xiaohang Fu; Liyuan Pan; Yanjing Wang (Frontiers in Cardiovascular Medicine)
BackgroundThis study examines the anatomical characteristics of the mitral isthmus (MI) and its spatial relationship with the esophagus in patients undergoing atrial fibrillation ablation, using cardiovascular computed tomographic angiography (CTA). Understanding this relationship is crucial to minimize the risk of esophageal injuries during ablation procedures.MethodsThe investigation included 300 participants, divided into 200 subjects in the experimental group undergoing atrial fibrillation ablation and 100 in the control group. Detailed CTA scans were used to assess the MI's structure and proximity to the esophagus, employing various measurements like the MI's endocardial length, depth, and its relation to adjacent esophageal anatomy.ResultsThe study revealed significant differences in the MI's length and distance measurements between the experimental and control groups, with the former showing greater dimensions, potentially influencing ablation strategies. A substantial proportion of patients exhibited close proximity or direct contact between the MI and the esophagus, emphasizing the importance of pre-procedural imaging in identifying risks for esophageal damage.ConclusionsPre-procedural cardiovascular CTA provides essential insights into the MI's anatomical details and its relation to the esophagus, aiding in the customization of ablation strategies to enhance procedural safety and efficacy. The findings highlight the significance of tailored imaging assessments to mitigate esophageal injury risks in atrial fibrillation ablation.